Electrical transport of SiNWs array after covalent attachment of new organic functionalities - Marianna Ambrico; Paolo Francesco Ambrico; Rosa di Mundo (Nanomaterials and Nanotechnology)
Modification of the electrical transport of a random network of silicon nanowires assembled on n‐ silicon support, after silicon nanowires functionalization by chlorination/alkylation procedure , is here described and discussed. We show that the organic functionalities induce charge transfer at single SiNW and produce doping‐like effect that is kept in the random network too. The SiNWs network also presents a surface recombination velocity lower than that of bulk silicon. Interestingly, the functionalized silicon nanowires/n‐Si junctions display photo‐yield and open circuit voltages higher than those including oxidized silicon nanowire networks. Electrical properties stability in time of junctions embedding propenyl terminated silicon nanowires network and transport modification after secondary functionalization is also shown. These results suggest a possible route for the integration of functionalized Si nanowires, although randomly distributed, in stable large area photovoltaic or molecule sensitive based devices.